Concept of Ikhlas, Semantic and Sufistic Perspective: Study of Tafsir Al Wajiz Wahbah Al Zuhaili and Ruhul Ma'ani Al Alusi - Hazuar; Idi Warsah; Fakhruddin; Aida Rahmi; A. Suardi (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This research examines the semantic dimensions of the term ikhlāṣ in the Qur’an and its interpretation within Sufi exegetical discourse. This study is motivated by the semantic development of ikhlāṣ, particularly the distinction between its lexical meaning and its technical-religious meaning in Islamic discourse. Addressing this issue academically is crucial, as a proper understanding of Ikhlas significantly influences a Muslim's practice of worship ( ubudiyyah ). The aim is to identify the interpretations and categories of Qur'anic verses related to Ikhlas through semantic and Sufi lenses. Using qualitative methods with a semantic approach, data were collected from various linguistic derivatives of the term in the Qur'an. This analysis uses Tafsir Al-Wajiz for contextual exploration and Tafsir Ruh Al-Ma'ani for Sufi depth. The findings indicate that although the masdar (gerund) form of Ikhlas is absent in the Qur'an, its conceptual essence exists through various noun and verb variants. This study concludes that Ikhlas encompasses two dimensions: the literal meaning in non-ritual contexts and the technical meaning related to worship, Such as the meanings of solitude, being chosen, pure milk, and other linguistic meanings. In the context of worship, ikhlas means purifying one's devotion solely for the sake of Allah. Furthermore, Sufi interpretation emphasizes spiritual depth, where the meaning of sincerity is shaped by the spiritual attainments of its practitioners.